The analysis of the effects of Liuwei Dihuang decoction on aging-related metabolites and metabolic pathways in naturally aging mice by ultra-performance liquid chromatography quadruple time-of-light mass spectrometry - Xi, W; Song, N; Yan, Q; Liang, H; Zhang, W (Journal of physiology and pharmacology : an official journal of the Polish Physiological Society, 2021)
Liuwei Dihuang decoction (LWDH) has been used to treat age-related diseases in Asia for thousands of years. Its effect is significant, but the mechanism is not entirely understood. The development and maturity of metabonomics technology have created a new way to understand its effects. In this study, 20-month-old naturally aging mice were used as the research subjects. Mice were randomly divided into the young group, elderly group, vitamin E group, and LWDH group, with 10 mice in each group. The UPLC-Q-TOF-MS technique analyzed the changes in plasma metabolism of these mice. Principal component analysis (PCA) and orthogonal partial least-squares discriminant analysis (OPLS-DA) were used to study metabolic markers and metabolic pathways. Compared with the elderly group, the organ index and weightbearing swimming time of the LWDH and vitamin E groups increased (P ≤ 0.01). The results show that LWDH can benignly regulate the expression level of 11 aging-associated metabolites in aged mice and alleviate the aging state of mice. These metabolites mainly affect the metabolism of glutathione, unsaturated fatty acid biosynthesis, pyrimidine, selenium, pentose phosphate, arginine, and proline.